Understanding tax morale and tax compliance of owner-managers of small companies - Yucedogru, Recep (2016)
Owner managers of small companies (OMSCs) present an important group for tax research, as they constitute a majority of taxpayers, although little is known about their tax compliance behaviour. Hence, the key purpose of this study is to understand how OMSCs’ tax compliance and tax morale, intrinsic motivation to pay taxes, are shaped through their social roles: as an individual and as a manager. Moreover, the study explores the influential factors on OMSCs’ tax morale such as religiosity. This study is particularly important for providing a detailed picture of the factors that are key to successful tax compliance, which might help OMSCs and policy design. Additionally, it is one of the first studies to understand OMSCs’ tax morale, particularly the first one in the context of Turkey, with a predominant by Muslim population. This study is based on three phases. First, the OMSCs’ tax morale model is developed building on the Theory of Planned Behaviour. In this phase, the factors that are grouped under Personal Norms, Corporate Norms and Perceived Behavioural Control are identified with the critical review of literature and their influences on OMSCs’ tax morale and tax compliance are discussed. Next, in the qualitative exploratory phase of the research, the model’s relevance to the research context is confirmed and necessary modifications to the model are made according to the results of the thematic analysis of 20 face to face interviews with OMSCs. The third phase comprised the confirmatory phase of the research. Based on 447 responses from an on-line survey, the model was tested using Structural Equation Modelling via Partial Least Squares. The results of this study show a strong positive relationship between tax morale and tax compliance of OMSCs. Interestingly, the most influential factor in predicting and explaining tax morale are Personal Norms, which refer to OMSCs’ personal beliefs and values, including religiosity. In contrast, Corporate Norms, which refer to normative beliefs of an OMSC about his/her company, were found to be affecting negatively on tax morale but in terms of magnitude are far less influential than Personal Norms. Perceived Behavioural Control positively influences tax morale but again to a smaller extent compared to Personal Norms. These findings suggest that OMSCs’ personal beliefs and values are the main determinant of their tax compliance behaviour rather than their corporate concerns. Overall, the current study illustrates how tax morale and tax compliance of OMSCs are shaped by using the model that utilises the factors that are discussed in the literature alongside additional factors that have emerged from the qualitative phase of this study. The model benefits policy makers by portraying OMSCs’ tax morale that might help policymakers to identify problems and aid them in devising policies to improve tax compliance of OMSC.